2012
DOI: 10.1007/s11274-012-1017-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamate-based colorimetric method for direct screening of transglutaminase-producing bacteria

Abstract: Microbial transglutaminase (MTGase) is a commercial enzyme that has been applied to many protein containing foods to improve their textural property. The screening of MTGase-producing microorganisms from various sources might lead to the discovery of a new MTGase with different characteristics. This report demonstrates the use of a direct detection method for MTGase-producing bacteria grown on an agar plate by filter paper disc (FPD) assay. The principle of the assay is the formation of a red burgundy color by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The literature reports on the potential use of plant materials such as soy, rice, maize and wheat flour, corn steep liquor, wheat middlings or malt extract as a source of nitrogen (Zhu et al 1995 ). Bourneow et al ( 2012 ) demonstrated that peptone was the best source of nitrogen for transglutaminase extraction from the Streptomyces sp. P20 and S .…”
Section: Biosynthesis Of Transglutaminasementioning
confidence: 99%
See 1 more Smart Citation
“…The literature reports on the potential use of plant materials such as soy, rice, maize and wheat flour, corn steep liquor, wheat middlings or malt extract as a source of nitrogen (Zhu et al 1995 ). Bourneow et al ( 2012 ) demonstrated that peptone was the best source of nitrogen for transglutaminase extraction from the Streptomyces sp. P20 and S .…”
Section: Biosynthesis Of Transglutaminasementioning
confidence: 99%
“…C2361 0.77 Bourneow et al ( 2001 ) Providencia sp. C1112 0.92 Bourneow et al ( 2001 ) Streptoverticillium mobaraense 0.9–3.4 Bourneow et al ( 2012 ); Zheng et al ( 2002 ); Zhu et al ( 1996 ); Gerber et al ( 1994 ); Ando et al ( 1989 ) Streptomyces platensis M5218 0.66 Lin et al ( 2006 ) Streptomyces hygroscopicus n/a Cui et al ( 2007 ) Streptomyces lividans n/a Lin et al ( 2004 , 2007 ) Streptomyces lividans JT46/pAE053 2.2 Lin et al ( 2006 ) Streptomyces lydicus 1.3 Bourneow et al ( 2001 ) Streptomyces platensis 1.4 Lin et al ( 2006 ); Bourneow et al ( 2001 ) Streptomyces sioyansis 3.3 Bourneow et al ( 2001 ) Streptoverticillium griseocarneum 1.46 Gerber et al ( 1994 ); Lin et al ( 2003 ) Streptoverticillium ladakanum NRRL–3191 0.28–1.55 Téllez-Luis et al ( 2004a , b ) Streptoverticillium sp. s–8112 1.46 Kanaji et al ( 1993 ) …”
Section: Introductionmentioning
confidence: 99%
“…Samples from Gadjah Mada University were firstly screened qualitatively using filter paper disc (FPD) method developed by Bourneow et al (2012) with slight modification. The positive colonies were then quantitatively assayed for their enzyme activity (Grossowicz et al, 1950) with slight modification.…”
Section: Screening Of Transglutaminase Producing Streptomycesmentioning
confidence: 99%